PENGARUH KONSENTRASI PUPUK ORRIN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN OKRA (Abelmoshus esculentus L. Moench) PADA KONDISI PEMBERIAN AIR YANG BERBEDA - Mayanti, Nur; Hemon, Farid; Priyono, Joko (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
Orrin fertilizer is a fertilizer commonly used by farmers because it contains all the nutrients that plants, including okra plants, needed. This research aimed to determine the effect of watering, orrin fertlizer concentration and the interaction between them on the growth and the yield of ocra plant. The experiment was held from August to November 2019 at Dusun Lengkok Embuk, Desa Mamben Lauk, Wanasaba, Lombok Timur. The experiment was designed according to used was a completely randomized design arranged factorially (2x5). The first factor was watering (75% and 100% field capacity). The second one was concentration of Orrin fertilizer application consist of 5 levels K0=0 ml/L water, K5=5 ml/L water, K10=10 ml/L water, K15=15 ml/L water, and K20=20 ml/L water with three replications, and thus resulted in 30 treatment pots. The data was analyzed by analysis of variance at 5% significance level. The result of the experiment showed that watering had significant effect only on the diameter of tube 30 day after transplanting (hspt) and the concentration of fertilizer did not have a significant effect on all tested parameters. In addition, the interaction between watering and fertilizer concentration significantly effected the height of the plant at 30 hspt.